Minimally conscious state “plus”: diagnostic criteria and relation to functional recovery - Thibaut, Aurore; Bodien, Yelena G.; Laureys, Steven; Giacino, Joseph T. (Journal of neurology, 2020)
Background We investigated the relationship between three language-dependent behaviors (i.e., command-following, intelligible verbalization, and intentional communication) and the functional status of patients with disorders of consciousness (DoC). We hypothesized that patients in minimally conscious state (MCS) who retain behavioral evidence of preserved language function would have similar levels of functional disability, while patients who lack these behaviors would demonstrate significantly greater disability. We reasoned that these results could then be used to establish empirically-based diagnostic criteria for MCS +. Methods In this retrospective cohort study we included rehabilitation inpatients diagnosed with DoC following severe-acquired brain injury (MCS = 57; vegetative state/unresponsive wakefulness syndrome [VS/UWS] = 63); women: 46; mean age: 47 ± 19 years; traumatic etiology: 68; time post-injury: 40 ± 23 days). We compared the scores of the Disability Rating Scale score (DRS) at time of transition from VS/UWS to MCS or from MCS – to MCS +, and at discharge between groups. Results Level of disability on the DRS was similar in patients with any combination of the three language-related behaviors. MCS patients with no behavioral evidence of language function (i.e., MCS –) were more functionally impaired than patients with MCS + at time of transition and at discharge. Conclusions Command-following, intelligible verbalization, and intentional communication are not associated with different levels of functional disability. Thus, the MCS + syndrome can be diagnosed based on the presence of any one of these language-related behaviors. Patients in MCS + may evidence less functional disability compared to those in MCS who fail to demonstrate language function (i.e., MCS –).